2020
DOI: 10.3892/etm.2020.8502
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA‑96 is associated with poor prognosis and promotes proliferation, migration and invasion in cholangiocarcinoma cells via MTSS1

Abstract: MicroRNA-96 (miR-96) has been revealed serve an oncogenic role in various types of cancer. However, the role of miR-96 in cholangiocarcinoma (CCA) development and progression is yet to be elucidated. Thus, the aim of the present study was to investigate the role of miR-96 in CCA. The expression pattern of miR-96 in CCA tissues and cell lines was evaluated using reverse transcription-quantitative PCR analysis. Kaplan-Meier curves and Cox regression analyses were conducted to investigate the prognostic significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
5
0
2
Order By: Relevance
“…Evidence indicates that some miRNAs function as oncogenes or tumor suppressors along with influencing various biological processes, such as cell proliferation, migration, invasion, differentiation, and apoptosis, especially in cancer cells (Yin et al, 2020). Promising results have been observed in the treatment of several neoplasms after using circulating miRNAs as predictors (Yin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence indicates that some miRNAs function as oncogenes or tumor suppressors along with influencing various biological processes, such as cell proliferation, migration, invasion, differentiation, and apoptosis, especially in cancer cells (Yin et al, 2020). Promising results have been observed in the treatment of several neoplasms after using circulating miRNAs as predictors (Yin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence indicates that some miRNAs function as oncogenes or tumor suppressors along with influencing various biological processes, such as cell proliferation, migration, invasion, differentiation, and apoptosis, especially in cancer cells (Yin et al, 2020). Promising results have been observed in the treatment of several neoplasms after using circulating miRNAs as predictors (Yin et al, 2020). The identification of molecular alterations in miRNAs and candidate genes for CCA biomarkers may contribute to clarify the molecular mechanisms involved in the pathogenesis of CCA, thus assisting with the early diagnosis of the disease and choosing new therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that miR-96-5p may bind to MTSS1. MiR-96 was upregulated in cholangiocarcinoma and positively associated with poor prognosis; its upregulation may promote cholangiocarcinoma cell proliferation, migration and invasion by targeting MTSS1 [ 49 ]. miR-96 has also been reported to be increased in breast cancer; its overexpression may suppress breast cancer cell migration by downregulating the expression of MTSS1 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Significant downregulation of miR‐215 was recorded in breast cancer tissues and cell lines 10 . On the other hand, miR‐96 oncogenic effect on breast cancer was elucidated via its role in promoting breast cancer cell proliferation, migration by silencing PTPN9 expression in an in vitro and in vivo studies 11 . Over expression of miR‐96 directly impaired cell apoptotic responsiveness by repressing FoxO1 expression 12 .…”
Section: Introductionmentioning
confidence: 99%
“…10 On the other hand, miR-96 oncogenic effect on breast cancer was elucidated via its role in promoting breast cancer cell proliferation, migration by silencing PTPN9 expression in an in vitro and in vivo studies. 11 Over expression of miR-96 directly impaired cell apoptotic responsiveness by repressing FoxO1 expression. 12 This study aims to elucidate the signaling cascade of M. on ceasing proliferation, survival and metastasis of experimentally induced Ehrlich solid tumor as a model of adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%